Microwave, ultrasound and ball mill procedures for bio-waste valorisation. Issue 2 (19th November 2014) - Tabasso, S.; Carnaroglio, D.; Calcio Gaudino, E.; Cravotto, G.
Abstract : Bio-waste valorisation has been one of the hottest research topics worldwide over the last decade. Abstract : Bio-waste valorisation has been one of the hottest research topics worldwide over the last decade. Following the biorefinery concept, the main goals have been the search for inexpensive renewable resources for the production of chemicals, materials and energy, the transformation of bio-waste into useful by-products and the development of new technologies for process intensification to make all these conversions economically profitable. Bio-waste is generally a negative-cost feedstock for the potential production of high value-added chemicals and bioenergy. The present review has the aim of describing existing studies and applications of non-conventional energy sources such as microwaves, ultrasound and ball milling within this field. We have focused our attention on suitable protocols for the conversion of biomass into fine chemicals. Comparisons with classic procedures are a good means with which to highlight the huge advantages and potential scalability of these so-called "enabling technologies".